M10 21G VS 22G EBUS-TBNA needle sampling and cell morphology of the core biopsies and needle washings: Is bigger better?. (14th November 2013) - Lockman, H; Medford, ARL; Bennett, JA
Abstract : Introduction: EBUS-TBNA has avoided the need for patients to undergo mediastinoscopy and can be done under conscious sedation with minimal complications for mediastinal lymph node sampling for lung cancer. The sample analysis varies depending on local expertice. Objective: To compare histology (core biopsy) vs. needle washing cytology in achieving a diagnosis of malignancy. Comparing biopsy results using 21G and 22G EBUS-TBNA needles. Methods: We reviewed all EBUS procedures performed at Glenfield Hospital, UK from 11 June 2008 till 24 April 2013. The results were then filtered to exclude the 1 st 10 procedures in view of the learning curve in performing the procedure and EBUS from 1 January 2010–31 December 2010 (period when the EBUS-TBNA needles were changed from 22G to 21G). Only confirmed diagnosis of malignancy from the remainder were analysed for the study. Results: 543 EBUS procedures were done in the 2 periods of which 234 yielded a diagnosis of malignancy (69 and 165 respectively). 68% of 22G needle core samples provided cell type morphology vs. 87% using the 21G needle. Needle washing only provided cell typing in 30% and 28%. The main cell types for the core biopsies were squamous cell carcinoma (19), adenocarcinoma (14) and small cell carcinoma (10) and in the 21G study adenocarcinoma (47), small cell carcinoma (34) and squamous cell carcinoma (28). Summary: The results show that switching from 22G to 21G EBUS-TBNA needles yielded a better diagnostic result in this study. Diagnosis based on cell types were also better using the 21G needles. Core biopsies gave better results compared to cytology from needle washings. Potentially depending on local practices we could consider performing diagnostic sampling analysis on needle core biopsies only and 21G EBUS-TBNA needles gave a better diagnostic yield.